2003
DOI: 10.1038/sj.jp.7211013
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Bone Ultrasound Velocity in Large-for-Gestational-Age Infants

Abstract: BACKGROUND:Bone speed of sound is a measure of bone breakability. There are few reports on bone mineral content in large for gestational age infants; most of them in infants of diabetic mothers. There are no data on bone speed of sound in large for gestational age infants of nondiabetic mothers. OBJECTIVE:To test the hypothesis that large for gestational age infants of nondiabetic mothers have lower bone speed of sound than appropriate for gestational age infants. DESIGN/METHODS:Bone speed of sound was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
0
17
2
1
Order By: Relevance
“…Our data also confirm previous studies that reported a correlation of bone quality with gestational age and birth weight both by DXA [23][24][25][26] and QUS. [9][10][11][12][13][14][15]27,28 Multivariate analysis confirmed postconceptional age as the most relevant predictor of bone quality. Body weight was the strongest predictor of QUS in the most immature infants but lost its significance in term neonates.…”
Section: Discussionmentioning
confidence: 90%
“…Our data also confirm previous studies that reported a correlation of bone quality with gestational age and birth weight both by DXA [23][24][25][26] and QUS. [9][10][11][12][13][14][15]27,28 Multivariate analysis confirmed postconceptional age as the most relevant predictor of bone quality. Body weight was the strongest predictor of QUS in the most immature infants but lost its significance in term neonates.…”
Section: Discussionmentioning
confidence: 90%
“…Measurements of bone SOS were obtained on the right tibia as previously described. [11][12][13][14] Using this instrument at the tibial site, our coefficients of variation (within-measurement and between-measurements) was below 0.5%.…”
Section: Biophysical Methodsmentioning
confidence: 97%
“…A negative relationship between size at birth and bone SOS was also indicated by lower tibial SOS values in LGA infants compared with AGA infants of non-diabetic mothers. 30 The investigators speculated that the lower SOS values in the larger infants may be due to reduced intrauterine fetal mobility in the space-constrained in utero environment of the LGA infant. Reduced spontaneous activity reportedly contributes to lower postnatal tibial SOS values, 34 while daily physical activity programs attenuate the longitudinal postnatal decrease in SOS values 35 and promote greater gain in bone mineral density in VLBW infants.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] In contrast, a recent tibial QUS study reported that term and preterm SGA newborn infants had higher SOS values than AGA infants, 29 indicating greater bone strength in SGA infants. In addition, tibial SOS values are reportedly lower in newborn infants who are large-for-gestational age (LGA) 30 and in infants whose mothers had gestational diabetes, 31 further suggesting an inverse correlation between size at birth and bone SOS.…”
Section: Introductionmentioning
confidence: 99%